Prove that if W₁ and W₂ are finite-dimensional subspaces of a vector space V, then W₁ + W₂ is finite-dimensional, and dim(W₁ + W₂) = dim(W₁) + dim(W₂) – dim(W₁ n W₂) - ... Hint: Let B₁ = (u₁,, uk) be a basis of W₁ n W2, hence dim W₁n W₂ k. Extending Bo into B₁ = (u1, ***, Uk, V1, ,U₁), a basis of W₁, we have dim W₁ k+ 1. Extending Bo into B2 = (u1, ..., uk, P1, * Pm), a basis of W2, we have dim W₂ = k + m. Therefore, it suffices to show that = = dim(W₁ + W₂) = k +l+m since dim(W₁) + dim(W₂) - dim(W₁ n W₂) = (k + 1) + (k + m) − k = k +l+m. Now let B = (u₁,· ···‚ Uk, U1, ***, VI, P1, …, pm). Show that B is a basis of W₁ + W₂ by proving: " 1. B spans W₁ + W₂ 2. B is linearly indepedent. 2

Elementary Linear Algebra (MindTap Course List)
8th Edition
ISBN:9781305658004
Author:Ron Larson
Publisher:Ron Larson
Chapter4: Vector Spaces
Section4.5: Basis And Dimension
Problem 69E: Find a basis for R2 that includes the vector (2,2).
icon
Related questions
Question
100%

Don't use chat gpt It Chatgpt means downvote 

Prove that if W₁ and W₂ are finite-dimensional subspaces of a vector space V, then W₁ + W₂ is
finite-dimensional, and
dim(W₁ + W₂) = dim(W₁) + dim(W₂) – dim(W₁ n W₂)
-
...
Hint: Let B₁ = (u₁,, uk) be a basis of W₁ n W2, hence dim W₁n W₂ k. Extending Bo
into B₁ = (u1, ***, Uk, V1,
,U₁), a basis of W₁, we have dim W₁ k+ 1. Extending Bo into
B2 = (u1, ..., uk, P1, * Pm), a basis of W2, we have dim W₂ = k + m. Therefore, it suffices to
show that
=
=
dim(W₁ + W₂) = k +l+m
since dim(W₁) + dim(W₂) - dim(W₁ n W₂) = (k + 1) + (k + m) − k = k +l+m.
Now let B = (u₁,·
···‚ Uk, U1, ***, VI, P1, …, pm). Show that B is a basis of W₁ + W₂ by proving:
"
1. B spans W₁ + W₂
2. B is linearly indepedent.
2
Transcribed Image Text:Prove that if W₁ and W₂ are finite-dimensional subspaces of a vector space V, then W₁ + W₂ is finite-dimensional, and dim(W₁ + W₂) = dim(W₁) + dim(W₂) – dim(W₁ n W₂) - ... Hint: Let B₁ = (u₁,, uk) be a basis of W₁ n W2, hence dim W₁n W₂ k. Extending Bo into B₁ = (u1, ***, Uk, V1, ,U₁), a basis of W₁, we have dim W₁ k+ 1. Extending Bo into B2 = (u1, ..., uk, P1, * Pm), a basis of W2, we have dim W₂ = k + m. Therefore, it suffices to show that = = dim(W₁ + W₂) = k +l+m since dim(W₁) + dim(W₂) - dim(W₁ n W₂) = (k + 1) + (k + m) − k = k +l+m. Now let B = (u₁,· ···‚ Uk, U1, ***, VI, P1, …, pm). Show that B is a basis of W₁ + W₂ by proving: " 1. B spans W₁ + W₂ 2. B is linearly indepedent. 2
Expert Solution
steps

Step by step

Solved in 2 steps with 4 images

Blurred answer
Similar questions
Recommended textbooks for you
Elementary Linear Algebra (MindTap Course List)
Elementary Linear Algebra (MindTap Course List)
Algebra
ISBN:
9781305658004
Author:
Ron Larson
Publisher:
Cengage Learning
Linear Algebra: A Modern Introduction
Linear Algebra: A Modern Introduction
Algebra
ISBN:
9781285463247
Author:
David Poole
Publisher:
Cengage Learning